Southern Senegal at the time of irragated banana farming : agricultural innovations and territorial dynamics - (:unkn) unknown (My University, 2017)
This thesis examines dessert banana cropping development induced territorial dynamics in the southern Senegal region, characterized by highly rained-dependent production systems and by a marginalization of the major national development dynamics. As an intensive and market-oriented crop, this agricultural innovation raises the question of its adoption in rain-fed systems, and above all its economic profitability in an isolation context and its interactions with local development dynamics. To answer this question, this thesis was based on data obtained from qualitative surveys of various banana sector stakeholders (producers, traders, supervisors, intermediaries, etc.) and a careful analysis of the ongoing changes in southern Senegal. The thesis is thus articulated on three axes. The first axis shows that the natural and socioeconomic factors that led to the event of irrigated banana cropping stems from the marginal nature of the southern regions of Senegal. The second part analyzes its integration process into farmers' the productive strategies while emphasizing on produces' organizations, banana production practices and marketing dynamics. Finally, an analysis of the socio-economic and geographical effects of banana cropping innovation dynamic development in southern Senegal, substituting banana innovation at the center of the ongoing socio-economic and environmental reorganizations bath at the local and regional levels. This thesis is thus a contribution to the study of "development operations" in rural Africa and the development opportunities of marginalized areas in West Africa.
Keywords: African Research